(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2026)
Background and Objective: Dyslipidemia, characterized by abnormal levels of total cholesterol (TC), low-density lipoprotein (LDL-C), high-density lipoprotein (HDL-C), and triglycerides (TG), is a major risk factor for cardiovascular diseases. Although the ketogenic diet (KD) is widely used as a very low-carbohydrate, high-fat therapeutic approach, its effects on lipid metabolism and cardiac health remain controversial. This study aimed to compare the impact of different types of ketogenic diets on serum lipid profile, atherogenic ratios, and cardiac histopathological changes in male albino rats. Methods: Thirty-five male albino rats were randomly divided into five groups of seven: a control group, a high-fat ketogenic diet (70% coconut oil), a high-fat ketogenic diet (70% animal fat), a high-protein ketogenic diet (35% casein, 60% coconut oil), and a cyclical ketogenic diet (70% coconut oil). The dietary intervention lasted for 50 days. At the end of the intervention, serum lipid parameters (TC, TG, LDL-C, HDL-C) and lipid ratios (TC/HDL-C, TG/HDL-C, LDL-C/HDL-C) were measured. Also, histopathological examination of heart tissue was performed using hematoxylin-eosin (H&E) staining. SPSS25 software was used for statistical analysis (p<0.05). Results: High-fat and high-protein diets significantly increased TC, TG, LDL-C, and VLDL levels in rats, with the coconut oil ketogenic diet showing the most adverse changes. HDL-C levels showed no significant changes across groups. Lipid ratios indicating atherogenic risk were increased dramatically in the high-fat and high-protein groups. Histological examinations of the heart in the coconut oil group showed fat accumulation, inflammatory cell infiltration, and cardiomyocyte destruction, while these changes were less severe in the animal fat group and were rarely observed in the control group. Conclusion: According to the results obtained, the effects of ketogenic diets are significantly influenced by the macronutrient composition, especially the fat source. High-fat diets, especially those enriched with coconut oil, have significant adverse effects on metabolic od lipids and cardiac tissue, while high-protein and periodic diets are considered comparatively safer, though further studies are needed to confirm their long-term effects. These findings highlight the importance of dietary fat composition when considering ketogenic diets for potential clinical use.